Hierarchical assessment of host factors influencing the spontaneous resolution of hepatitis C infection - Provazzi, Paola Jocelan Scarin [UNESP]; Rossi, Livia Maria Gonçalves [UNESP]; Carneiro, Bruno Moreira [UNESP]; Miura, Valeria Chamas [UNESP]; Rosa, Plinio Cesar Rodrigues [UNESP]; de Carvalho, Lucas Rodrigues [UNESP]; de Andrade, Stephane Tereza Queiroz [UNESP]; Fachini, Roberta Maria; Grotto, Rejane Maria Tommasini [UNESP]; Silva, Giovanni Faria [UNESP]; Valêncio, Carlos Roberto [UNESP]; Neto, Paulo Scarpelini [UNESP]; et al. (Springer Nature, 2019)
Background: Hepatitis C virus (HCV) infection is associated with chronic liver disease, resulting in cirrhosis and hepatocellular carcinoma. Approximately 20% of HCV infections are spontaneously resolved. Here, we assessed the hierarchical relevance of host factors contributing to viral clearance. Methods: DNA samples from 40 resolved infections and 40 chronic HCV patients paired by age were analyzed. Bivariate analysis was performed to rank the importance of each contributing factor in spontaneous HCV clearance. Results: Interestingly, 63.6% of patients with resolved infections exhibited the protective genotype CC for SNP rs12979860. Additionally, 59.3% of patients with resolved infections displayed the protective genotype TT/TT for SNP ss469415590. Moreover, a ranking of clearance factors was estimated. In order of importance, the IL28B CC genotype (OR 0.197, 95% CI 0.072–0.541) followed by the INFL4 TT/TT genotype (OR 0.237, 95% CI 0.083–0.679), and female gender (OR 0.394, 95% CI 0.159–0.977) were the main predictors for clearance of HCV infection. Conclusions: HCV clearance is multifactorial and the contributing factors display a hierarchical order. Identifying all elements playing role in HCV clearance is of the most importance for HCV-related disease management. Dissecting the relevance of each contributing factor will certainly improve our understanding of the pathogenesis of HCV infection.
Keywords: HCV; Hepatitis C; IL28B; MAVS; SNP rs12979860